ANALISIS TINDAK TUTUR DALAM NOVEL SURAT KECIL UNTUK TUHAN KARYA AGNES DAVONAR BERDASARKAN TEORI AUSTIN - Ni Kadek Sri Sandra Dewi; IGA Putu Tuti Indrawati; Ida Ayu Made Wedasuwari (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2023)
This study examines the analysis of pragmatics seen from the aspect of speech acts. The purpose of this research is to find out the speech acts based on Austin's theory which in Austin's theory there are three speech acts namely locution, illocution and perlocution in the novel Surat Kecil Untuk Tuhan by Agnes Davonar. In this research, data collection method is used, namely observation method, reading method, and note-taking method. The data analysis method used in this research is by reducing data, presenting data, verifying data, and concluding data. The results obtained in the research of speech acts in the novel Surat Kecil Untuk Tuhan by Agnes Davonar are forty-seven utterances including nineteen locutionary speech acts, namely fifteen statement locutions, two question locutions and two command locutions. In illocutionary speech acts there are eighteen utterances including two representative illocutions, two commissive illocutions, eight directive illocutions, five expressive illocutions and one declarative illocution. Then, in perlocutionary speech acts there are ten numbers of utterances. The factors that cause the occurrence of speech acts in the novel Surat Kecil Untuk Tuhan by Agnes Davonar are telling something informative, conveying criticism or satire, honesty or insistence, conveying prohibition.